The Strength of Semantic Meaning Related to Image Schema Theory (Raparin Journal of Humanities (RJH), 2025)
The impact of semantic meaning, in the act of communication and understanding, plays the most important role in the power of influence for the recipient and the transmission of the speaker/reader's message. This study titled "The Strength of Semantic Meaning Related to Image Schema Theory," examines the power of words in delivering the speaker/writer's ideas and thoughts to the recipient and influence the other. In this study, the semantic power of a word was analyzed according to the theory of the image scheme, which is generally based on the concept of non-literal words and through which the strong meaning of the word is determined in terms of semantic meaning.The study focuses, in its two sections, on showing the theory of the image scheme and the power of the word’s meaning on the speaker's experience convention, so that the human being, depending on the accumulation of his/her experiences and draws a pattern of the image of his perception of the world in his/her mind, which becomes the basis for how words are conventionalized.The outline of the image in the Kurdish language in the terminology of the language has been reflected in both everyday speech and various texts such as poetry, philosophy, politics and economics. Consequently, this makes the power of concepts produced by emotional experience, perception of experiences and the movement of the speaker to be more than lexical words with the literal meaning.